Mass cytometry reveals cellular fingerprint associated with IgE+ peanut tolerance and allergy in early life - Melanie R. Neeland (Nature Portfolio, 2020)
Food allergy is triggered by IgE, but some individuals are not allergic to peanuts despite making peanut-specific IgE, and are considered peanut-tolerant. Here, the authors identify differences in blood immune cell composition of peanut-allergic and tolerant infants using mass cytometry, which may help uncover the mechanism of allergic tolerance.